Effect of High Peroxide Value Fats on Performance of Broilers in an Immune Challenged State - McGill, J.; McGill, E.; Kamyab, A.; Firman , J.D. (International Journal of Poultry Science, 2011)
A floor pen trial was conducted to determine the effect of high peroxide value fats on the performance of broilers in an immune challenged state. Ross 708 broilers were randomly assigned to 48 floor pens with each pen containing 30 birds. Dietary treatments were developed as a 3 x 2 factorial using three levels of fat rancidity, with Peroxide Values (PV) of 0, 75 and 150. One half of each peroxide value diet also received an antioxidant at 125 ppm. Six dietary treatments with eight replicates were fed to broilers from hatch to day 49. Diets were formulated based on standard industry diets with the exception of fat being forced into the diet at 3% for the starter ration (0-3 wks), 6% in the grower ration (3-5 wks) and 6% in the finisher ration (5-7 wks). At 4 weeks of age the broilers underwent a coccidial challenge. The trial measured the performance of the immune challenged broilers based on the parameters of Feed Intake (FI), Body Weight Gain (BWG) and feed conversion (F:G). An initial pen weight was taken on day 0 for each of the 48 pens. Birds were weighed at 3, 5 and 7 weeks of age to calculate F:G. At week 7, four birds per pen (32 birds/treatment) were sacrificed and processed in order to obtain a fat pad weight, carcass weight, percent meat yield and cecal scoring. The results indicated that birds consuming diets with a peroxide value of 75 or greater exhibited poorer feed conversion than the treatment with an acceptable peroxide value. Furthermore, diets with the added antioxidant demonstrated no statistical difference in feed conversion due to peroxide value. There were also no significant effects of the immune challenge in combination with peroxide levels on bird performance.